Oncology patients follow-up in the Family Health Strategy: a literature review (Research, Society and Development, 2022)
The role of healthcare professionals in a cancer patient´s home have paramount importance. The multidisciplinary team present in the Family Health Strategy (ESF) has the ability to provide the creation of a very important bond, not only with the patient with cancer but also with their family nucleus. The creation of this bond establishes co-responsibility with the community and enables comprehensive care by offering alternatives that positively affect the patient´s scenario and its social cycle. Thus, this study analyzes the importance of the ESF in prevention, screening and palliative care support in cancer patients, associating with possible positive impacts of a good relationship between the patient, family, ESF and the oncology team.